A Study of Structural Parameters Effects on Pressure Differential to Roll Titanium Diaphragm for a Spacecraft Propellant Tank. (8th November 2022) - Ma, Tianju; Gu, Sendong; Zhao, Jipeng; Yu, Bin; Zhang, Jianjun; Yang, Wenbo
Abstract : A range of titanium diaphragms for spacecraft propellant tanks are designed in detail, and two typical titanium diaphragms were manufactured and corresponding reversal tests were developed. A series of finite element models of the reversal process of these titanium diaphragms is developed based on the arc-length method and a finite element analysis software. With the aid of the models, this paper analyzes the characteristics of pressure drop during the whole reversal process and investigates the effects of the structural parameters on pressure differential to roll titanium diaphragm. The results show that simulated values of the critical pressure and the overturning pressure show good agreement with measured ones. In addition, the critical pressure increases with increasing thickness, decreasing bottom diameter and chamfering radius. The thickness and the bottom diameter are the main influence factors for the critical pressure. The overturning pressure increases with increasing thickness and arc radius. These effects of the bottom diameter, the chamfering radius, and arc radius become sharper with increasing thickness.